Effect of oral vitamin E supplementation on lipid profile in diabetes mellitus: evidence based case report - Indah Sri Wulandari; Krisadelfa Sutanto (World Nutrition Journal, 2024)
Introduction: Diabetes mellitus, a prominent non-communicable disease, presents as a chronic condition associated with various complications, including heart disease, nerve damage, chronic kidney disease, and dyslipidemia. A pivotal abnormality in diabetic dyslipidemia is insulin resistance, which stimulates the production of Hepatic VLDL1 (very-low-density lipoprotein 1). The resulting overproduction of VLDL1 is metabolically linked to an abundance of small, dense LDL (low-density lipoprotein) particles and a reduction in large, cholesterol-rich HDL2 (high-density lipoprotein). Conversely, vitamin E, known for its antioxidant and anti-inflammatory properties, acts as a remover of peroxyl radicals, preventing lipid oxidation and safeguarding polyunsaturated fatty acids (PUFA) within cells and plasma lipoproteins. Method: This study investigates the impact of oral vitamin E supplementation on the lipid profile in diabetic patients. Employing advanced search techniques on databases like PubMed, Cochrane Library, and Google Scholar, we conducted a comprehensive literature search using MeSH terms, advanced search methods, and specific eligibility criteria. The results yielded one systematic review with a meta-analysis and two randomized controlled trials (RCTs) that met the predefined PICO and eligibility criteria. Results: The systematic review and meta-analysis, along with one RCT, reported no significant reduction in lipid profiles with oral vitamin E supplementation in diabetic patients. In contrast, the other RCT observed an improvement in lipid profiles among diabetic patients receiving oral vitamin E supplementation. Conclusion: Supplementing with oral vitamin E does not enhance the lipid profile of individuals with diabetes mellitus.